An Introduction to the Cape d'Aguilar Marine Reserve, Hong Kong - Morton, Brian (Book collections on Project MUSE., 1995)
The shores of Hong Kong are geologically diverse and have been shaped by wind, rain and sea to produce a wide array of seascapes, from towering cliffs in the southeast and on many wave-battered islands, to wide expanses of mud in the northwest. Fringed by tropical mangroves, such mudflats are home to the secretive denizens of water-logged bunows and are patrolled by vast flocks of wading birds that arcive in Hong Kong each spring and autumn to exploit its resident productivity. The Mai Po Marshes Nature Reserve is such a protected habitat and seascape. Most (80%) of Hong Kong's shores are, however, of rock and wave and have not generated the same interest and support for their continued survival. Survival is, however, becoming increasingly important because even the outermost reaches of Hong Kong's tentorial waters are now under the pervasive threat of pollution. No piece of coast in Hong Kong has escaped the attentions of inshore fishermen, who collect a great arcay of marine life for consumption. Urban settlements are spreading out from the city centres and, along with other coastal developments such as the new port and airport, refuse tips, power stations and docks and jetties, there are the insidious effects of the vast quantities of urban sewage, agricultural effluents, industrial contaminants and construction wastes that this city generates and disperses into its sureounding sea, often at the shoreline.